Optimizing the Strategic Communication of Gerbas Tani Community in Developing Tourist Village in Kedungrejo, Rowokangkung, Lumajang - Alhimni Fahma; Achmad Arifulin Nuha (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2023)
Gerbas Tani stands for Gerakan Belanja Sayur dari Lahan Petani, which was born in 2018, marked by the educational activity "Petik Tomat" for kindergarten students. The mascot of Gerbas Tani is a 0.1-hectare flower garden in the middle of a 2.5-hectare vegetable garden. The total number of visitors when the flower garden is in bloom reaches 20,000 people, with an average of 30-50 visitors per day. However, due to the pandemic, vegetable sales have stopped, and tour visitors are limited. The mentoring process was carried out through the Asset Based Community Development (ABCD) approach through the stages of discovery, dream, design, define, and destiny to optimize strategic communication to develop the potential of Gerbas Tourism Village. The results of this service have successfully encouraged the Gerbas Tani Community to become a solid community to preserve the tourist village through persuasive communication. Gerbas Tani members become actors of change collectively in order to realize a sustainable and developing village through the development of online sales while maintaining offline sales. They consistently hold different tourism activities three times a year as a solution to developing a tourist village after the Pandemic. The findings highlight the importance of strategic communication in empowering local communities, strengthening partnerships, and promoting sustainable economic development in the context of tourism villages.